ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI WILAYAH PELAYANAN INSTALASI PENGOLAHAN AIR GUNUNG TUGEL PDAM TIRTA SATRIA BANYUMAS - Verrdy Chrisna Primandani; Novi Andhi Setyo Purwono; Atiyah Barkah (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
Clean water is a vital thing that is needed by humans for their survival. Clean water is used by humans for various activities such as bathing, washing, cooking, and other needs. The increasing number of residents in the South Purwokerto SPAM area certainly makes the need for clean water also increase. Due to the increasing demand for water which is not matched by additional water sources, people often complain about water with a small discharge or even not flowing at all. This research was conducted to find out how much clean water is needed, and to find out how much clean water is available at the South Purwokerto SPAM. In this study, an analysis of the need and availability of clean water is carried out for the next 25 years or until 2045, with several methods that will be used, namely the Geometric, Arithmetic, and Linear Regression Methods. Based on the results of the analysis, it is known that the need for clean water in the South Purwokerto SPAM area in 2045 is 351.69 liters/second, the maximum daily requirement is 422.03 liters/second, and the water demand at peak hours is 562.70 liters/second. The availability of existing water does not increase every year, the available water debit is 130 liters/second and has not been able to meet the clean water needs of the community in the South Purwokerto SPAM Region.